Zachowania zdrowotne studentów Fizjoterapii = Health behaviors of students of Physiotherapy - Mariusz Baumgart; Magdalena Weber-Rajek; Agnieszka Radzimińska; Aleksander Goch; Walery Zukow (Kazimierz Wielki University, 2015)
Baumgart Mariusz, Weber-Rajek Magdalena, Radzimińska Agnieszka, Goch Aleksander, Zukow Walery. Zachowania zdrowotne studentów Fizjoterapii = Health behaviors of students of Physiotherapy. Journal of Education, Health and Sport. 2015;5(6):211-224. ISSN 2391-8306. DOI 10.5281/zenodo.18554 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A211-224 https://pbn.nauka.gov.pl/works/565694 http://dx.doi.org/10.5281/zenodo.18554 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 10.06.2015.   Zachowania zdrowotne studentów Fizjoterapii Health behaviors of students of Physiotherapy   Mariusz Baumgart1, Magdalena Weber-Rajek2, Agnieszka Radzimińska2, Aleksander Goch2, Walery Zukow3   1. Uniwersytet Mikołaja Kopernika w Toruniu, Collegium Medicum w Bydgoszczy, Katedra i Zakład Anatomii Prawidłowej, Bydgoszcz, Polska 2. Uniwersytet Mikołaja Kopernika w Toruniu Collegium Medicum w Bydgoszczy Katedra Fizjoterapii, Bydgoszcz, Polska 3. Uniwersytet Kazimierza Wielkiego, Bydgoszcz, Polska   Autor do korespondencji dr. n.med. Mariusz Baumgart e-mail baumgartmar@gmail.com   Streszczenie   Styl życia jest głównym determinantem zdrowia. Wczesna dorosłość jest najlepszym okresem dla osiągnięcia długotrwałych korzyści z wyboru zdrowego trybu życia. Jednakże wyniki badań dotyczących zachowań zdrowotnych młodzieży prowadzonych w Polsce i na świecie nie są zadawalające. Celem pracy była ocena zachowań zdrowotnych młodzieży studiującej  na kierunku Fizjoterapia. Badania miały także na celu określenie, czy istnieje różnica w zachowaniach zdrowotnych między kobietami i mężczyznami. Średni wynik kwestionariusza IZZ dla całej badanej grupy wynosi 6,76 sten, co stanowi granicę między wynikami  średnimi a wysokimi. W całej badanej grupie najlepsze wyniki uzyskano w kategorii "prawidłowe nawyki żywieniowe", najgorsze w kategorii "praktyki zdrowotne". Nie wykazano różnic istotnych statystycznie w wynikach zachowań zdrowotnych między kobietami i mężczyznami.   Summary   Life style is the main health determiner. Early adulthood is the best period for achieving long-term advantages by choosing healthy life style. However, the results of the research concerning health behaviours of the young people done in Poland and in the world are not satisfactory. The aim of the study was to assess health behaviors among young people studying Physiotherapy. The aim of the study was also to determine whether there is a difference in health behaviours among women and men. An average IoHB result for the entire examined group amounts to 6.76 sten which is the upper limit for average results. The best IoHB questionnaire results were obtained in the category "proper nutrition habits", the worst in the category "health practices". It has not been demonstrated statistically significant differences between men and women.   Słowa kluczowe: zachowania zdrowotne, studenci, fizjoterapia. Keywords: health behaviors, students, physiotherapy.